Teori Basis Ekspor Masa Kini di Arab Saudi - Siti Sutriah Nurzaman (Journal of Regional and City Planning, 2008)
It seems that Export Base Theory particularly in the natural resource export base case is considered as an obsolete theory and barely discussed again in planning journals. This paper tries to revisit the application of economic base concept for Arab Saudi case. Data, references and observation of Saudi Arabia case, strongly proof that Saudi Arabia has developed successfully implementing development concept that heavily rely on this theory. The five year development plans of Saudi Arabia shows a very strong influence of the theory. Many regions in Indonesia show similarity to Arab Saudi in which has prosperous natural resources. They can take lessons to imitate the succes of Arab Saudi.